Haematological and Biochemical Parameters of Captive Siberian Tigers (Panthera tigris altaica) from the Heilongjiang Province, China. Issue 3 (13th December 2020) - Liu, Enqi; Ma, Liying; You, Dan; Yang, Cen; Hu, Yawen; Xu, Haitao; Liu, Dan; Wang, Yajun
Abstract: Haematological and biochemical parameters play important roles in safeguarding animal health and preventing disease, but the blood reference values of many wild animals are still unknown. Recently, few descriptions of the blood parameters of Siberian tigers ( Panthera tigris altaica ) have been reported because these tigers comprise an endangered species; however, it is extremely difficult to obtain blood samples necessary for these analyses. This study presents 14 haematological and 16 biochemical parameters of 133 Siberian tigers, of which 112 and 21 were from Heilongjiang Siberian Tiger Park (HB) and Hailin Siberian Tiger Park (HD), China, respectively. Our study is the first to determine the following parameters in Siberian tigers: red blood cell volume distribution width, platelet count, mean platelet volume, amylase (AMY), sodium/potassium, globulin and albumin/globulin levels. As the data for total bilirubin and AMY were not statistically significant, no statistical analysis was conducted for these parameters. Few parameters were significantly different according to sex and region ( p  < 0.05). The concentration of alkaline phosphatase decreased with age, whereas the creatinine (CREA) increased with age. The CREA concentration of tigers raised in HB was much lower than that of tigers raised in HD. The data obtained in this study provide a reference for monitoring the health of wild and captive Siberian tigers and will add important information to the standards for haematological and biochemical parameters of wild felines. Abstract : This study collected and analysed the haematological and biochemical parameters of 133 Siberian tigers; these data can provide a reference for monitoring the health of wild and captive Siberian tiger.